AQUASPINING AS ANTI-STRESS HEALTH PREVENTION - Dimitar Trendafilov; Bistra Dimitrova (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
In a nutshell SPA is something old and good, but nowadays enriched with the miraculous impact of the water culture and aqua practices. But in our opinion is very important to know that the SPA is the health prevention of a healthy people for their recovery from social and professional everyday stress. In most European countries and it became another kind of SPA effects called a short - Medical SPA. Our working hypothesis is based on the assumption that the development of modules for practicing aquaspinning will allow to optimize the proposed relaxing and procreative prevention programs and promoting the health and beauty. The aim of this study was to determine the specificity of the effects aquaspinning through the application of current methods of prevention and health promotion.